Fabrication and morphological characterization of hybrid polymeric solar cells based on P3HT and inorganic nanocrystal blends - Toong, Way Yun; Khaulah Sulaiman (Universiti Kebangsaan Malaysia, 2011)
In this research we investigated the effect of composition on the fabrication and morphological characteristics of a hybrid polymeric solar cell which consists of an electron donating conjugated polymer, namely is poly(3-hexylthiophene) (P3HT) combined with an electron-accepting component, which is a type of inorganic compound of TiO2 nanocrystals. The composition of TiO2 in the blends is varied and the optimum performance of the devices are studied. The optical and morphological characterizations are carried out via UV-Visible absorption spectroscopy, X-ray diffraction (XRD), atomic force microscopy (AFM) and scanning electron microscopy (SEM). The electrical characteristics of the devices are measured by using Keithley 2400 SMU and solar simulator with light intensity of 100 mW/cm2